Probable extinction of the western black rhino, Diceros bicornis longipes: 2006 survey in northern Cameroon - Isabelle Lagrot; Jean-François Lagrot; Paul Bour (Pachyderm)
From 25 January to 8 June 2006, the NGO Symbiose and veterinarians Isabelle and Jean-François Lagrot with their local teams patrolled the distribution area of Diceros bicornis longipes in northern Cameroon to assess the status of the last population of the western black rhino subspecies. Over 46 field patrols were organized in the area situated roughly between Faro National Park on the western border and Bouba Ndjida National Park on the eastern border, totalling over 2500 km of patrol effort. Using historical data, results of previous surveys, information from a network of villagers and cooperation with trophy-hunting guides, the fieldwork carried out during the dry season concluded that no reliable sign of rhino presence was found to attest to the survival of the western black rhino. The estimation of around 30 individuals produced by Symbiose in August 2004 was based on fake rhino tracks, which some of the trackers had made to preserve their jobs. Following this survey, the African Rhino Specialist Group of the International Union for the Conservation of Nature, Species Survival Commission, modified the official status for D.b. longipes. Thus far classified as Critically Endangered with 5 confirmed individuals in 2001, it has now been declared Probably Extinct. Symbiose continued the survey through the rainy season until the end of 2006. Despite 23 additional field patrols, no reliable sign of rhino presence was found.